2006
DOI: 10.1111/j.1432-2277.2006.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two dosages of thymoglobulin used as a short-course for induction in kidney transplantation

Abstract: Summary Thymoglobulin is used effectively as an induction agent in kidney transplantation, but the optimal dose is not well established. We evaluated the degree and durability of T‐cell clearances with two different thymoglobulin regimens in adult kidney transplant recipients (KTR). Seven KTR received a 3‐day thymoglobulin‐based induction of 1.0 mg/kg/day while nine received 1.5 mg/kg/day, in addition to maintenance immunosuppression. Lymphocyte subsets were monitored for 6 months. Renal function, infections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 25 publications
3
41
0
1
Order By: Relevance
“…Patients were generally low-risk and this study did show the efficacy of induction therapy (low dose) with a short course of rATG. In an attempt to establish an optimal dose, Wong et al [108] evaluated the degree and durability of T-cell clearances with two different thymoglobulin regimens in adult kidney transplant recipients: group I had a 3-day thymoglobulin-based induction of 1.0 mg/kg/day, while group II received 1.5 mg/kg/day in addition to maintenance immunosuppression. They concluded that thymoglobulin induction was efficacious in both groups, but with a significantly sustained T-cell clearance in the 1.5-mg/kg/day regimen up to the first 6 months post-induction therapy.…”
Section: Dosing Of Thymoglobulinmentioning
confidence: 99%
“…Patients were generally low-risk and this study did show the efficacy of induction therapy (low dose) with a short course of rATG. In an attempt to establish an optimal dose, Wong et al [108] evaluated the degree and durability of T-cell clearances with two different thymoglobulin regimens in adult kidney transplant recipients: group I had a 3-day thymoglobulin-based induction of 1.0 mg/kg/day, while group II received 1.5 mg/kg/day in addition to maintenance immunosuppression. They concluded that thymoglobulin induction was efficacious in both groups, but with a significantly sustained T-cell clearance in the 1.5-mg/kg/day regimen up to the first 6 months post-induction therapy.…”
Section: Dosing Of Thymoglobulinmentioning
confidence: 99%
“…11 The literature suggests that induction totaling 6 mg/kg, administered in divided doses of 1-2 mg/kg over 3-5 days, may provide the best balance of immunosuppression and risk of infection. 10,11,[14][15][16] rATG induction versus no induction Two large, randomized controlled trials have examined rATG induction regimens versus noninduction regimens 17 There were no differences between the treatment groups with regard to mean cold ischemia time, cytomegalovirus status of donor and recipient, or values for human leukocyte antigen mismatch. The number of patients with a panel reactive antibody grade greater than 50% was significantly higher only in the ATG with cyclosporine group (P=0.044).…”
mentioning
confidence: 99%
“…77 Wong et al reported a total rATG dose of only 3 mg/kg was found to have similar rejection rates (0% reported in a total of 16 patients treated) to 4.5 mg/kg dose and equal renal function at 2 years. 78 The patients in these studies were not considered high immunological risk. But Peddi et al described high immunological risk kidney and kidney-pancreas recipients receiving rATG based on CD3 counts, with each patient getting an average of 4.2 mg/kg (or three 1.5 mg/kg doses) with good safety profile, low rates of rejection, and cost savings because of less rATG used.…”
Section: Dose and Administrationmentioning
confidence: 99%